Night Vision Patrolling Rover Navigation System for Women’s Safety Using Machine Learning - Gopalakrishnan, K.; Thiruvenkatasamy, S.; Prabhakar, E.; Aarthi, R. (International Journal of Psychosocial Rehabilitation, 2019)
Women safety is the biggest threat to India. There are many areas in which women are not feeling safe. This should be changed as much soon as possible. Technology changes and improves day by day to change the way human are living. So this paper focuses on updating technology framework to make stronger women safety mechanism. In this paper, we introduce a new security mechanism to safeguard women during abnormal activities. New security mechanism has been proposed based on the patrolling robot using the Raspberry Pi. Here night vision camera can be used for securing any premises. To improve the accuracy of the classifier, various machine learning models are used. Algorithms like Boosting, Bagging, Stacking and Enhanced reweight mechanism in Ensemble are used. Confusion matrix with individual classifier accuracy is considered for evaluating results. The results show that the proposed method performs well compared to existing algorithms.